Storage characteristics of fish balls from rohu, Labeo rohita at - 20ÂºC - Dutta, C (Indian Journal of Fisheries, 2011)
The storage characteristics of fish balls prepared from minced rohu meat at -20 ÂºC upon treatment with cryoprotectants such as sorbitol (4%), sucrose (4%) and sodium tripolyphosphate (0.3%) were studied. The levels of different parameters like salt soluble nitrogen (SSN), total volatile base nitrogen (TVBN) and free fatty acid during storage period were observed to be within the acceptable limits. The product treated with cryoprotective agents had a better acceptability compared to control group.